A new genus and species of the family Archipsyllidae (Insecta: Paraneoptera: Permopsocida) from the Late Triassic of Queensland - Lambkin, Kevin J. (Zootaxa, 2018)
The dedicated collecting of Robert Knezour of Ipswich continues to uncover remarkable finds in the Late Triassic (Norian) Dinmore fossil insect locality of south-east Queensland. The latest discovery is a forewing of the extinct family Archipsyllidae, described herein as Dinmopsylla semota gen. et sp. nov., the first record of the family from the Triassic and from the southern hemisphere.